Gene co‐expression analysis reveals transcriptome divergence between wild and cultivated chickpea under drought stress. (7th October 2020) - Moenga, Susan M.; Gai, Yunpeng; Carrasquilla‐Garcia, Noelia; Perilla‐Henao, Laura M.; Cook, Douglas R.
Summary: Ancestral adaptations in crop wild relatives can provide a genetic reservoir for crop improvement. Here we document physiological changes to mild and severe drought stress, and the associated transcriptome dynamics in both wild and cultivated chickpea. Over 60% of transcriptional changes were related to metabolism, indicating that metabolic plasticity is a core and conserved drought response. In addition, changes in RNA processing and protein turnover were predominant in the data, suggestive of broad restructuring of the chickpea proteome in response to drought. While 12% of the drought‐responsive transcripts have similar dynamics in cultivated and wild accessions, numerous transcripts had expression patterns unique to particular genotypes, or that distinguished wild from cultivated genotypes and whose divergence may be a consequence of domestication. These and other comparisons provide a transcriptional correlate of previously described species' genetic diversity, with wild accessions well differentiated from each other and from cultivars, and cultivars essentially indistinguishable at the broad transcriptome level. We identified metabolic pathways such as phenylpropanoid metabolism, and biological processes such as stomatal development, which are differentially regulated across genotypes with potential consequences on drought tolerance. These data indicate that wild Cicer reticulatum may provide both conserved and divergent mechanisms as a resource in breeding for drought tolerance in cultivated chickpea. Significance Statement: Wild relatives of crops have the potential to expand both the breadth and nature of agronomic traits in their related crop species. By differential expression and co‐expression analysis, we document both conserved and diverged expression patterns in wild and cultivated chickpea gene families involved in plant development, metabolism and signaling. Here we identify genes and biological processes that are candidates for breeding for drought tolerance in the chickpea crop.